Self-liganded Suzuki-Miyaura coupling for site-selective protein PEGylation. - Dumas, A; Spicer, C; Gao, Z; Takehana, T; Lin, Y; Yasukohchi, T; Davis, B (2013)
Building with PEGs: PEG-boronic acids, in the presence of simple Pd sources, are capable of acting as direct and effective Suzuki reagents in 70-98 % yield. When combined with non-natural amino acids, they allow efficient and direct, site-selective PEGylation of proteins at predetermined positions under biologically compatible conditions without the need for exogenous ligands. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.